Phosphor powder, composite and light-emitting device
Patent Information
- Application Number
- JP2023509020
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-22
- Filing Date
- 2022-03-11
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2042-03-11
AI Technical Summary
【0010】 本発明の蛍光体粉末を用いることで、白色LEDの輝度を向上させることができる。
Smart Images

Figure 0007638367000004 
Figure 0007638367000005 
Figure 0007638367000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a phosphor powder, a composite, and a light-emitting device. [Background technology]
[0002] In order to manufacture white LEDs, research is being conducted on red phosphors that convert blue light from a blue LED chip into red light. Known red phosphors are those expressed by the general formula MAlSiN3 (where M is one or more elements selected from the group consisting of Mg, Ca, Sr, Ba, and Eu). Incidentally, phosphors where M is Ca are often written as "CASN", and phosphors where M contains two elements, Sr and Ca, are often written as "SCASN". As a specific example, Patent Document 1 discloses a compound represented by the general formula M a Sr b Ca c Al d S e N f It contains a crystalline phase represented by 4000 mW / mm 2 The phosphor is characterized by having a quantum efficiency maintenance rate of 85% or more when excited by light. In this general formula, M represents an activation element, and 0 <a<0.05、0.95≦b≦1、0≦c<0.1、a+b+c=1、0.7≦d≦1.3、0.7≦e≦1.3、2.5≦f≦3.5である。 [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-077800 A Summary of the Invention [Problem to be solved by the invention]
[0004] Various improvements have been made to the red phosphor that converts the blue light from a blue LED chip into red light, but there is still room for improvement in terms of brightness when used as a white LED. For example, in constructing a white LED package, a red phosphor is often used in combination with other phosphors (usually yellow to green phosphors). Therefore, it is preferable that a good luminance is obtained not only in terms of the performance of the red phosphor itself but also in terms of the "combination" of the red phosphor with other phosphors.
[0005] The present invention has been made in view of the above circumstances. One of the objects of the present invention is to improve the brightness of white LEDs by improving the red phosphor. [Means for solving the problem]
[0006] The present inventors have completed the invention provided below.
[0007] According to the present invention, The general formula (Sr x ,Ca 1-x-y ,EU y A phosphor powder made of a red phosphor represented by the formula: AlSi(N,O)3, x<1, 1-xy>0, The cumulative 10% value in the volume-based particle size distribution curve of the phosphor powder is D 10 , cumulative 50% value D 50 , cumulative 90% value D 90 Then, D 50 The value of is greater than 20 μm and less than or equal to 40 μm, (D 90 -D 10 ) / D 50 The value of phosphor powder is 1.12 or less. is provided.
[0008] Further, according to the present invention, A composite material comprising the above phosphor powder and a sealing material that seals the phosphor powder. is provided.
[0009] Further, according to the present invention, A light emitting element that emits excitation light; The above complex that converts the wavelength of the excitation light; A light emitting device comprising: is provided. Effect of the Invention
[0010] By using the phosphor powder of the present invention, the brightness of a white LED can be improved. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a diagram for explaining a presumed mechanism by which the use of the phosphor powder of the present embodiment makes it possible to improve the brightness of a white LED. [Diagram 2] FIG. 1 is a diagram for explaining a conventional white LED package. [Diagram 3] 1 is a schematic cross-sectional view showing an example of the structure of a light-emitting device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. In all drawings, similar components are given similar symbols and descriptions thereof are omitted where appropriate. In order to avoid complexity, (i) when there are multiple identical components in the same drawing, only one of them is given a reference symbol and not all of them, or (ii) especially in Figure 2 and subsequent figures, components similar to those in Figure 1 are not given a reference symbol again. All drawings are for illustrative purposes only. The shapes and dimensional ratios of each component in the drawings do not necessarily correspond to the actual objects.
[0013] In this specification, unless otherwise specified, the expression "X to Y" in the explanation of a numerical range means from X to Y. For example, "1 to 5% by mass" means "from 1% by mass to 5% by mass."
[0014] In this specification, LED is an abbreviation for Light Emitting Diode.
[0015] <Phosphor powder> The phosphor powder of this embodiment has the same crystal phase as CaAlSiN3 and is represented by the general formula (Sr x ,Ca 1-x-y ,EU y )AlSi(N,O)3, where x<1, 1-xy>0. The cumulative 10% value in the volume-based particle size distribution curve of the phosphor powder of this embodiment is D 10 , cumulative 50% value D 50 , cumulative 90% value D 90 Then, D 50 The value of is greater than 20 μm and less than or equal to 40 μm, (D 90 -D 10 ) / D 50 The value of is 1.12 or less.
[0016] As mentioned above, when constructing a white LED package, a red phosphor is often used in combination with other phosphors (usually yellow to green phosphors). Typically, a white LED package includes a composite in which a mixture of a red phosphor and other phosphors is sealed with a sealing material. White light can be obtained by irradiating the composite with blue light from a blue LED chip.
[0017] The present inventors hypothesized that the "distribution" or "uniform distribution" of the red phosphor and other phosphors in the above-mentioned composite might be related to the luminance of a white LED. Specifically, in the design of normal white LEDs, the amount of red phosphor used is often less than other phosphors, so if the red phosphor is uniformly dispersed in the composite, blue light is not sufficiently converted to red light, which is thought to be an obstacle to improving brightness. Based on this idea, in order to improve brightness, it was thought that it would be better to unevenly distribute the red phosphor 10 in the light emitting device 100 (white LED package) near the light emitting element 120 (emitting blue light) as shown in Figure 1, so that blue light is preferentially converted to red light.
[0018] The present inventors have developed the above-mentioned idea and proposed a specific solution, D 50 They thought that it would be possible to prepare a red phosphor 10 with a relatively large particle size and a relatively sharp particle size distribution, and to form a composite by mixing the red phosphor 10 with another phosphor 20 and an encapsulant 30. In other words, they thought that by forming a composite using a red phosphor that is "large and sinks easily" compared to commonly used yellow to green phosphors (YAG, LuAG, etc.), it would be possible to realize the phosphor particle distribution state shown in Figure 1, and improve the brightness of white LEDs.
[0019] The present inventors have 50 Specifically, D 50 is greater than 20 μm and less than 40 μm, and is an index showing the sharpness of the particle size distribution (D 90 -D 10 ) / D 50 A phosphor powder (comprising a red phosphor) having a value of 1.12 or less was newly produced. By using this new phosphor powder (red phosphor) in combination with other phosphors to manufacture the light emitting device 100 (white LED package), it has become possible to improve the brightness.
[0020] For reference, in a conventional light emitting device 100 (white LED package), a red phosphor having a relatively small particle size and / or a relatively wide particle size distribution was used, and therefore the distribution of the red phosphor 10 and the other phosphors 20 was thought to be, for example, as shown in Figure 2.
[0021] By the way, D 50 The upper limit of 40 μm has the advantage of being able to prevent clogging of the nozzle used when injecting or applying a mixture of the sealing resin and phosphor particles into the package.
[0022] The phosphor powder of the present embodiment can be obtained by appropriately selecting the raw materials, the usage ratio of each raw material, the manufacturing procedure and manufacturing conditions, etc. Regarding the selection of raw materials and the quantitative ratio of raw materials, preferably, a larger amount of Sr-containing raw material is used, and the "core" described later is added, etc. Regarding the manufacturing procedure and manufacturing conditions, preferably, firing is performed using a container made of a high melting point metal (for example, a container made of tungsten, molybdenum, or tantalum), and the firing time is made relatively long, etc. These details will be described later.
[0023] Continue the description of the phosphor powder of the present embodiment.
[0024] (Crystal structure, elemental composition, etc.) The phosphor powder of the present embodiment is composed of a red phosphor represented by the general formula (Sr x , Ca 1-x-y , Eu y )AlSi(N, O)3, which has the same crystal phase as CaAlSiN3. In this general formula, x < 1 and 1 - x - y > 0. Here, (N, O) indicates that a part of N is inevitably substituted by O.
[0025] The crystal phase can be confirmed by powder X-ray diffraction. A single crystal phase of the crystal is preferred for the crystal phase, but it may contain different phases as long as it does not have a significant impact on the phosphor characteristics. The presence or absence of different phases can be determined, for example, by the presence or absence of peaks other than those due to the target crystal phase by powder X-ray diffraction. The skeletal structure of CaAlSiN3 is composed of the bonding of (Si, Al)-N4 tetrahedrons, and Ca atoms are located in the gaps of the skeleton. A part of Ca 2+ is substituted by Eu 2+ acting as a luminescence center to become a red phosphor.
[0026] Regarding x, preferably 0.9 < x < 1, more preferably 0.92 < x < 1, and still more preferably 0.95 < x < 1. As the finding of the present inventors, it is preferable that the amount of Sr in the phosphor particles of the present embodiment is larger in terms of improving luminance and other performance.
[0027] Regarding y, preferably y < 0.1, more preferably 0.0005 < y < 0.1, and even more preferably 0.001 < y < 0.05. In terms of good internal quantum efficiency and emission intensity, the value of y is preferably adjusted appropriately.
[0028] (Particle size distribution) As described above, for the phosphor powder of this embodiment, the D 50 value may be greater than 20 μm and not more than 40 μm. The D 50 value is preferably not less than 25 μm and not more than 40 μm, more preferably not less than 25 μm and not more than 35 μm, and particularly preferably not less than 30 μm and not more than 35 μm. Also, as described above, (D 90 - D 10 ) / D 50 value may be not more than 1.12. This value is preferably not more than 1.11, and more preferably not more than 1.10. (D 90 - D 10 ) / D 50 has no particular lower limit value, but from a practical aspect such as manufacturing cost, the lower limit is, for example, 1.05.
[0029] The value of D 10 itself is preferably not less than 10 μm and not more than 20 μm, and more preferably not less than 15 μm and not more than 19 μm. The value of D 90 itself is preferably not less than 30 μm and not more than 60 μm, more preferably not less than 40 μm and not more than 60 μm, and even more preferably not less than 45 μm and not more than 60 μm.
[0030] Also, in this embodiment, the cumulative 97% value D 97 in the volume-based particle size distribution curve is preferably not less than 50 μm and not more than 100 μm, and more preferably not less than 60 μm and not more than 90 μm. Also, in this embodiment, the cumulative 100 value D 100 in the volume-based particle size distribution curve is preferably not less than 80 μm and not more than 200 μm, and more preferably not less than 100 μm and not more than 180 μm. By ensuring that these values are not too large, for example, clogging of a nozzle used when injecting or applying a mixture of sealing resin and phosphor particles into a package can be suppressed.
[0031] The particle size distribution can be measured on a volume basis by a laser diffraction scattering method. The measurement is usually performed in a wet state. For details of the sample pretreatment method and the measurement conditions, please refer to the Examples below.
[0032] <Method of manufacturing phosphor powder> The phosphor powder of this embodiment can be obtained by appropriately selecting the raw materials, the ratio of each raw material, the manufacturing procedure, the manufacturing conditions, etc. A mixing step of mixing the starting materials to form a raw material mixture powder; A sintering process for sintering the raw material powder mixture to obtain a sintered product; The phosphor powder can be produced through the steps. In addition, the phosphor powder may be produced through additional steps other than those described above.
[0033] The mixing step, the firing step, and additional steps other than these steps will be described below.
[0034] (Mixing process) In the mixing step, the starting materials are mixed to form a raw material mixed powder. Examples of starting materials include europium compounds, strontium compounds such as strontium nitride, calcium compounds such as calcium nitride, silicon nitride, and aluminum nitride. Each of the starting materials is preferably in powder form.
[0035] Examples of europium compounds include oxides containing europium, hydroxides containing europium, nitrides containing europium, oxynitrides containing europium, halides containing europium, and the like. These can be used alone or in combination of two or more. Among these, it is preferable to use europium oxide, europium nitride, and europium fluoride alone, and it is more preferable to use europium oxide alone.
[0036] In the firing process, europium can be divided into those that dissolve, those that volatilize, and those that remain as heterogeneous components. The heterogeneous components containing europium can be removed by acid treatment or the like. However, if too much is generated, components insoluble in acid treatment are generated, and the luminance decreases. Also, if it is a heterogeneous phase that does not absorb excess light, it may remain as it is, and europium may be contained in this heterogeneous phase.
[0037] The amount of the europium compound used is not limited, but it is preferably used in an amount such that y in the above general formula satisfies y < 0.1, more preferably 0.0005 < y < 0.1, and even more preferably 0.001 < y < 0.05.
[0038] On the other hand, regarding the amount of the strontium compound, it is preferably used in an amount such that x in the above general formula satisfies 0.9 ≦ x < 1, more preferably 0.92 ≦ x < 1, and even more preferably 0.95 ≦ x < 1. D 50 or (D 90 -D 10 ) / D 50 In terms of obtaining a phosphor powder with a desired value, in this embodiment, it is preferable that the amount of strontium is relatively large.
[0039] In this embodiment, the starting material (mixed raw material powder) preferably contains SCASN phosphor core particles having a median diameter of 5 μm or more and 30 μm or less. In other words, a part of the starting material is preferably SCASN phosphor core particles having a median diameter of 5 μm or more and 30 μm or less. The median diameter is more preferably 10 μm or more and 20 μm or less. In this specification, the SCASN phosphor core particle is also referred to simply as a "core particle" or "core".
[0040] Although the details are unclear, it is believed that by using core particles, crystallization will proceed from the core particles in the subsequent firing process. For this reason, it is believed that the way crystals grow will be different from when the firing process is carried out without using core particles (for example, it is believed that the use of core particles will promote crystal growth, making it easier to obtain larger particles, and suppressing the generation of extremely large or small particles). And, perhaps as a result, D 50 The value of is greater than 20 μm and less than or equal to 40 μm, (D 90 -D 10 ) / D 50 It is considered that it becomes easier to obtain a phosphor powder having a value of 1.12 or less.
[0041] The core particles may be, for example, a red phosphor represented by the same general formula as the phosphor powder of the present embodiment described above. In other words, the core particles may be, for example, D 50 The value of is not necessarily greater than 20 μm and not greater than 40 μm, and / or (D 90 -D 10 ) / D 50 Although the value of is not 1.12 or less, the composition is the same as or similar to that of the phosphor powder of this embodiment.
[0042] When core particles are used, the amount thereof is, for example, 1 mass % or more and 20 mass % or less, preferably 2 mass % or more and 15 mass % or less, more preferably 2 mass % or more and 10 mass % or less, and even more preferably 2 mass % or more and 7 mass % or less, based on the total amount of the raw material mixed powder.
[0043] The core particles can be obtained, for example, through a process substantially similar to that of the phosphor powder of this embodiment. That is, in the manufacturing process of the phosphor powder of this embodiment, the core particles can be obtained in a substantially similar manner except that the core particles are not added in the mixing process. The composition (general formula) of the core particles is also preferably the same as that of the phosphor powder of this embodiment.
[0044] In the mixing step, the raw material mixed powder can be obtained, for example, by a method of dry mixing the starting materials, or a method of wet mixing in an inert solvent that does not substantially react with each starting material, followed by removing the solvent. As a mixing device, for example, a small mill mixer, a V-type mixer, a rocking mixer, a ball mill, a vibration mill, etc. can be used. After mixing using the device, the raw material mixed powder can be obtained by removing aggregates using a sieve as necessary. In order to prevent deterioration of the starting materials and unintended inclusion of oxygen, the mixing step is preferably carried out in a nitrogen atmosphere or in an environment with as little moisture (humidity) as possible.
[0045] (Firing process) In the firing step, the raw material powder mixture obtained in the mixing step is fired to obtain a fired product. The firing temperature in the firing step is preferably 1800°C or higher and 2100°C or lower, and more preferably 1900°C or higher and 2000°C or lower. When the firing temperature is equal to or higher than the lower limit, the grain growth of the phosphor particles proceeds more effectively. Therefore, the light absorptance, internal quantum efficiency, and external quantum efficiency can be further improved. When the firing temperature is equal to or lower than the upper limit, the decomposition of the phosphor particles can be further suppressed. Therefore, the light absorptance, internal quantum efficiency, and external quantum efficiency can be further improved. Other conditions in the firing step, such as the temperature rise time, temperature rise rate, heating retention time, and pressure, are not particularly limited and may be appropriately adjusted depending on the raw materials used. 50In order to make the particle size larger than 20 μm, the heating and holding time is typically preferably 10 hours or more and 30 hours or less, more preferably 12 hours or more and 30 hours or less. The pressure is preferably 0.6 MPa or more and 10 MPa or less (gauge pressure). From the viewpoint of controlling the oxygen concentration, the firing step is preferably carried out in a nitrogen gas atmosphere. That is, the firing step is preferably carried out in a nitrogen gas atmosphere with a pressure of 0.6 MPa or more and 10 MPa or less (gauge pressure).
[0046] In firing, it is preferable to heat the mixture by filling it into a container that is unlikely to react with the mixture during firing, such as a high-melting point metal container, specifically a container whose inner wall is made of tungsten, molybdenum, or tantalum, which can suppress the generation of heterogeneous phases.
[0047] (Powderization process) As an additional step, a powdering step may be performed. The fired product obtained through the firing step is usually granular or lumpy. When the fired product is lumpy and difficult to handle, the fired product can be made into a powder by using a single or a combination of processes such as crushing, grinding, and classification. A specific processing method includes, for example, pulverizing the sintered body to a predetermined particle size using a general pulverizer such as a ball mill, a vibration mill, a jet mill, etc. However, care should be taken because excessive pulverization may produce fine particles that easily scatter light or may cause crystal defects on the particle surface, resulting in a decrease in luminous efficiency.
[0048] (Annealing process) An annealing step may be performed as an additional step. Specifically, after the firing step, an annealing step may be performed in which the fired powder is annealed at a temperature lower than the firing temperature in the firing step to obtain an annealed powder. The annealing step is preferably carried out in a non-oxidizing atmosphere other than pure nitrogen, such as an inert gas, such as a rare gas or nitrogen gas, a reducing gas, such as hydrogen gas, carbon monoxide gas, hydrocarbon gas, or ammonia gas, or a mixture of these, or in a vacuum, etc. It is particularly preferably carried out in a hydrogen gas atmosphere or an argon atmosphere. The annealing step may be performed under atmospheric pressure, under pressure, or under reduced pressure. The heat treatment temperature in the annealing step is preferably 1300° C. to 1400° C. The duration of the annealing step is not particularly limited, but is preferably 3 hours to 12 hours, more preferably 5 hours to 10 hours. The annealing process can improve the luminous efficiency of the phosphor particles sufficiently, and also improve the transparency by removing distortions and defects due to the rearrangement of the elements. The annealing process may result in the generation of heterogeneous phases, but these can be sufficiently removed by the process described below.
[0049] (Acid treatment process) An acid treatment step may be performed as an additional step. In the acid treatment step, the annealed powder obtained in the annealing step is usually treated with acid. This makes it possible to remove at least a part of the impurities that do not contribute to light emission. Incidentally, it is presumed that the impurities that do not contribute to light emission are generated during the firing step and the annealing step.
[0050] The acid may be an aqueous solution containing one or more acids selected from hydrofluoric acid, sulfuric acid, phosphoric acid, hydrochloric acid, and nitric acid. In particular, hydrofluoric acid, nitric acid, and a mixed acid of hydrofluoric acid and nitric acid are preferred. The acid treatment can be carried out by dispersing the annealed powder in an aqueous solution containing the above-mentioned acid. The stirring time is, for example, from 10 minutes to 6 hours, preferably from 30 minutes to 3 hours. The stirring temperature can be, for example, from 40°C to 90°C, preferably from 50°C to 70°C. After the acid treatment step, the liquid in which the annealed powder is dispersed may be subjected to a boiling treatment. After the acid treatment step, substances other than the phosphor powder are separated by filtration, and if necessary, substances adhering to the phosphor particles may be washed with water. After washing with water, the phosphor powder is usually dried by natural drying or drying in a dryer. The dried phosphor powder may be placed in a crucible and heated to modify the surface.
[0051] Through the series of steps as described above, the phosphor powder of this embodiment can be obtained.
[0052] <Complex> The composite includes, for example, the phosphor powder of this embodiment and a sealant that seals the phosphor powder. In the composite, the above-mentioned phosphor powder is dispersed in the sealant. As described above, in application to a white LED, the composite preferably includes the phosphor powder of this embodiment (described above) and another phosphor powder different from it. The "other phosphor powder" is usually a yellow to green phosphor, specifically, YAG phosphor, LuAG phosphor, β-SiAlON phosphor, etc. The ratio of the phosphor powder of this embodiment to the other phosphor powder in the composite is, for example, phosphor powder of this embodiment: other phosphor powder = 1:99 to 50:50, specifically 1:99 to 30:70, more specifically 1:99 to 10:90, in mass ratio.
[0053] The sealing material may be a known material such as resin, glass, ceramics, etc. Examples of the resin that may be used for the sealing material include transparent resins such as silicone resin, epoxy resin, and urethane resin.
[0054] The composite may be produced by adding phosphor powder to a liquid sealing material (resin, glass, ceramics, etc.), mixing the mixture uniformly, and then curing or sintering the mixture by heat treatment. In this case, when a composite is produced by sealing (i) the phosphor powder of this embodiment and (ii) a commonly used YAG phosphor, LuAG phosphor, β-SiAlON phosphor, etc., with a liquid sealing material, the phosphor powder of this embodiment tends to be unevenly distributed at the bottom of the composite.
[0055] <Light emitting device> 3 is a schematic cross-sectional view showing an example of the structure of a light emitting device 100. As shown in FIG. 3, the light emitting device 100 includes a light emitting element 120, a heat sink 130, a case 140, a first lead frame 150, a second lead frame 160, a bonding wire 170, a bonding wire 172, and a composite 40.
[0056] The light emitting element 120 is mounted in a predetermined region on the upper surface of the heat sink 130. By mounting the light emitting element 120 on the heat sink 130, it is possible to improve the heat dissipation properties of the light emitting element 120. Note that a packaging substrate may be used instead of the heat sink 130.
[0057] The light emitting element 120 is a semiconductor element that emits excitation light. For example, an LED chip that emits light with a wavelength of 300 nm to 500 nm, which corresponds to near ultraviolet to blue light, can be used as the light emitting element 120. One electrode (not shown) disposed on the upper surface side of the light emitting element 120 is connected to the surface of the first lead frame 150 via a bonding wire 170 such as a gold wire. The other electrode (not shown) formed on the upper surface of the light emitting element 120 is connected to the surface of the second lead frame 160 via a bonding wire 172 such as a gold wire.
[0058] A generally funnel-shaped recess whose hole diameter gradually increases from the bottom surface toward the top is formed in the case 140. The light emitting element 120 is provided on the bottom surface of the recess. The wall surface of the recess surrounding the light emitting element 120 serves as a reflector.
[0059] The composite 40 is filled in the recess whose wall is formed by the case 140. The composite 40 is a wavelength conversion member that converts the excitation light emitted from the light emitting element 120 into light with a longer wavelength. The composite of the present embodiment described above is used as the composite 40. In FIG. 3, the composite 40 is composed of phosphor particles 1 and a sealing material 30. Preferably, the phosphor powder (red phosphor) of the present embodiment is unevenly distributed in the lower part of the composite 40. Also, preferably, other phosphors (typically YAG phosphor, LuAG phosphor, β-SiAlON phosphor, etc.) are unevenly distributed in the upper part of the composite 40. That is, preferably, among the multiple phosphor particles 1 shown in FIG. 3, those located relatively lower are the phosphor powder (red phosphor) of the present embodiment, and those located relatively higher are other phosphor particles.
[0060] 1 shows a surface-mounted light-emitting device, but the light-emitting device is not limited to the surface-mounted type. The light-emitting device may be a bullet type, a COB (chip-on-board) type, a CSP (chip-scale package) type, or the like.
[0061] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. EXAMPLES
[0062] The embodiments of the present invention will be described in detail based on Examples and Comparative Examples. It should be noted that the present invention is not limited to the Examples.
[0063] <Example of core particle production> First, 60.60 g of α-type silicon nitride (Si3N4, Ube Industries, SN-E10 grade), 53.12 g of aluminum nitride (AlN, Tokuyama Corporation, E grade), and 7.30 g of europium oxide (Eu2O3, Shin-Etsu Chemical Co., Ltd.) were placed in a container and premixed. Next, in a glove box maintained in a nitrogen atmosphere with a moisture content of 1 mass ppm or less and an oxygen concentration of 50 ppm or less, 2.75 g of calcium nitride (Ca3N2, manufactured by Materion) and 116.23 g of strontium nitride (Sr3N2, purity 2N, manufactured by Kojundo Chemical Laboratory Co., Ltd.) were further placed in the container and dry mixed. As a result, a raw material powder (mixed powder) was obtained.
[0064] In a glove box, 240 g of the raw material powder was filled into a tungsten container with a lid. After closing the lid of the container, it was removed from the glove box and placed in an electric furnace equipped with a carbon heater. Then, the electric furnace was evacuated sufficiently until the pressure inside was 0.1 PaG or less. While continuing the vacuum evacuation, the temperature in the electric furnace was raised to 600°C. After reaching 600°C, nitrogen gas was introduced into the electric furnace, and the pressure in the electric furnace was adjusted to 0.9MPaG. Then, in a nitrogen gas atmosphere, the temperature in the electric furnace was raised to 1950°C, and after reaching 1950°C, heat treatment was performed for 8 hours. Then, heating was terminated and the material was cooled to room temperature. After cooling to room temperature, red lumps were collected from the container. The collected lumps were crushed and sieved in a mortar, and the particle size was adjusted to a median diameter of 17 μm.
[0065] <Production of phosphor powder> Example 1 (1) 57.20 g of α-type silicon nitride (Si3N4, Ube Industries, SN-E10 grade), 50.14 g of aluminum nitride (AlN, Tokuyama Corporation, E grade), 6.89 g of europium oxide (Eu2O3, Shin-Etsu Chemical Co., Ltd.), and 12.00 g of the core particles with a median diameter of 17 μm prepared above were placed in a container and premixed.
[0066] (2) Next, in a glove box maintained in a nitrogen atmosphere with a moisture content of 1 mass ppm or less and an oxygen concentration of 50 ppm or less, 1.09 g of calcium nitride (Ca3N2, manufactured by Materion) and 112.68 g of strontium nitride (Sr3N2, purity 2N, manufactured by Kojundo Chemical Laboratory Co., Ltd.) were further weighed and dry-mixed into the above container. This resulted in a raw material powder (mixed powder).
[0067] (3) In a glove box, 240 g of the raw material powder was filled into a tungsten container with a lid. After closing the lid of the container, it was removed from the glove box and placed in an electric furnace equipped with a carbon heater. Then, the electric furnace was evacuated sufficiently until the pressure inside was 0.1 PaG or less.
[0068] (4) While continuing the evacuation, the temperature inside the electric furnace was raised to 600°C. After reaching 600°C, nitrogen gas was introduced into the electric furnace and the pressure inside the electric furnace was adjusted to 0.9 MPa·G. The temperature inside the electric furnace was then raised in a nitrogen gas atmosphere until it reached 1950°C, and heat treatment was continued for 15 hours after reaching 1950°C. Heating was then terminated and the material was allowed to cool to room temperature. After cooling to room temperature, a red lump was collected from the container.
[0069] (5) The collected lumps were crushed and passed through a sieve with 75 μm openings. Then, the lumps were crushed under the conditions of 0.15 MPa × 20 g / min using a JM crusher (manufactured by Nisshin Engineering Inc., model number: SJ-100C-CB). In this way, a red phosphor (fired powder) was obtained.
[0070] (6) The obtained fired powder was filled into a tungsten container and quickly transferred to an electric furnace equipped with a carbon heater, and the furnace was fully evacuated until the pressure inside the furnace was 0.1 PaG or less. Heating was started while continuing the evacuation, and when the temperature reached 600°C, argon gas was introduced into the furnace and the pressure of the atmosphere inside the furnace was adjusted to atmospheric pressure. The temperature continued to rise to 1350°C even after the introduction of argon gas was started. After the temperature reached 1350°C, the heat treatment was carried out for 8 hours. After that, heating was stopped and the material was cooled to room temperature. After cooling to room temperature, the powder after the annealing treatment was collected from the container. The collected powder was passed through a sieve to adjust the particle size. In this way, a red phosphor (annealed powder) was obtained.
[0071] (7) The annealed powder was put into 2.0M hydrochloric acid at room temperature so that the slurry concentration was 25% by mass, and soaked for 1 hour. This resulted in an acid treatment. After the acid treatment, the hydrochloric acid slurry was boiled for 1 hour while stirring. The boiled slurry was cooled to room temperature and filtered to separate the acid treatment liquid from the synthetic powder. The synthetic powder after separation of the acid treatment liquid was placed in a dryer set at a temperature range of 100°C to 120°C for 12 hours. The dried powder after the acid treatment step was filled into an alumina crucible, heated in air at a heating rate of 10°C / min, and heat-treated at 400°C for 3 hours. After heat treatment, it was left to cool to room temperature.
[0072] In this manner, the phosphor powder of Example 1 was obtained.
[0073] The obtained phosphor sample was subjected to powder X-ray diffraction using CuKα radiation using an X-ray diffractometer (Ultima IV manufactured by Rigaku Corporation). The obtained X-ray diffraction pattern was identical to that of CaAlSiN3 crystals, and it was confirmed that the main crystal phase had the same crystal structure as CaAlSiN3 crystals.
[0074] Comparative Example 1 A phosphor powder was obtained in the same manner as in Example 1, except for the following changes. (i) The amounts of each material mixed when obtaining the raw powder were Si3N4: 60.39 g, AlN: 52.94 g, Eu2O3: 8.41 g, Ca3N2: 2.43 g, and Sr3N2: 115.83 g, and no core particles were used. (ii) The heat treatment time at 1950°C was 8 hours instead of 15 hours.
[0075] Comparative Example 2 A phosphor powder was obtained in the same manner as in Example 1, except that the amounts of each material mixed when obtaining the raw material powder were Si3N4: 57.57 g, AlN: 50.46 g, Eu2O3: 6.93 g, Ca3N2: 2.62 g, and Sr3N2: 110.42 g.
[0076] Comparative Example 3 The powder obtained by the process up to step (7) of Example 1 was classified using a sieve with an opening of 45 μm, and the residue on the sieve was taken as the phosphor powder of Comparative Example 3.
[0077] The amounts of core particles added, the molar ratios of each element, and the general formula (Sr x ,Ca 1-x-y ,EU y The correspondence between x, 1-xy, and y in AlSi(N,O)3, and the heating (firing) conditions (the conditions of step (4) in Example 1) are shown below.
[0078]
Table 1
[0079] <Particle size distribution measurement> Measurement was carried out by the laser diffraction scattering method in accordance with JIS R1629:1997 using Microtrac MT3300EX II (manufactured by Microtrac Bell Co., Ltd.). 0.5 g of phosphor powder was added to 100 cc of ion-exchanged water, and dispersion treatment was performed thereon with an Ultrasonic Homogenizer US-150E (manufactured by Nippon Seiki Co., Ltd., chip size φ20 mm, Amplitude 100%, oscillation frequency 19.5 KHz, amplitude approximately 31 μm) for 3 minutes, and then particle size measurement was carried out with MT3300EX II. From the obtained particle size distribution, D 50 , (D 90 - D 10 ) / D 50 etc. were determined. The results were summarized in Table 2.
[0080]
Table 2
[0081] <Fabrication of LED package and evaluation of luminance> The phosphor powder obtained in the examples or comparative examples was added to a silicone resin together with a YAG phosphor (manufactured by DAEJOO ELECTRONIC MATERIALS CO., LTD., trade name DLP-GY25A1, peak wavelength 530.4 nm, median diameter: 21.5 μm), and defoaming and kneading were performed to obtain a kneaded product. This kneaded product was potted in a surface mount type package joined with a blue LED element having a peak wavelength of 450 nm, and further thermally cured to fabricate a white LED. Here, the addition amount ratio of the phosphor and the YAG phosphor was adjusted so that the chromaticity coordinates (x, y) of the white LED became (0.380, 0.380) during electroluminescence (the specific addition amount ratio is described in Table 3). The total luminous flux of the fabricated white LED when it was energized and emitted was measured using a total luminous flux measuring device manufactured by Otsuka Electronics Co., Ltd. (a device combining a 500 mm diameter integrating hemisphere and a spectrophotometer / MCPD-9800). This measurement was performed on 10 white LEDs with chromaticity x ranging from 0.370 to 0.390 and chromaticity y ranging from 0.370 to 0.390, and the average of the 10 measured values was used as the final measured value. This evaluation result was a relative evaluation when the average value of the total luminous flux of the white LEDs fabricated using the phosphor powder of Comparative Example 1 was set as 100%.
[0082] [Table 3]
[0083] As shown in Table 3, D 50 is greater than 20 μm and less than or equal to 40 μm, (D 90 -D 10 ) / D 50 By using a phosphor powder (red phosphor) with a value of 1.12 or less, a white LED with improved brightness could be obtained.
[0084] This application claims priority based on Japanese Patent Application No. 2021-047031, filed on March 22, 2021, the disclosure of which is incorporated herein in its entirety. [Explanation of symbols]
[0085] 10 Red phosphor 20 Other phosphors 30 Encapsulating material 40 Complex 100 Light emitting device 120 Light emitting element 130 Heat sink 140 cases 150 First lead frame 160 Second lead frame 170 Bonding Wire 172 Bonding Wire
Claims
1. CaAlSiN 3 The general formula (Sr x , Ca 1-x-y , Eu y )AlSi(N,O) 3 A phosphor powder made of a red phosphor represented by the formula: x<1, 1-x-y>0, The cumulative 10% value in the volume-based particle size distribution curve of the phosphor powder is D 10 , cumulative 50% value D 50 , cumulative 90% value D 90 When this is done, D 50 The value of is 30 μm or more and 40 μm or less, (D 90 -D 10 ) / D 50 The phosphor powder has a value of 1.05 or more and 1.12 or less.
2. The phosphor powder according to claim 1 , A phosphor powder having a fluorescence spectrum with a peak wavelength of 600 to 650 nm when irradiated with blue excitation light with a wavelength of 455 nm.
3. The phosphor powder according to claim 1 or 2, A phosphor powder in which y<0.
1.
4. A composite comprising the phosphor powder according to any one of claims 1 to 3 and a sealant that seals the phosphor powder.
5. A light emitting element that emits excitation light; The composite according to claim 4, which converts the wavelength of the excitation light; A light emitting device comprising:
Citation Information
Patent Citations
Preparation method of nitride red fluorescent powder
CN111187617A
Powdered phosphor, method for producing the same, luminescent device, and lighting system
JP2006257353A
Light-emitting device, display device, and lighting device
JP2013201434A
Nitride fluorescent material, and light emitting device
JP2017210626A
Phosphor, light-emitting device, illumination device and image display device
JP2019077800A